Assessing community health governance for evidence-informed decision-making: a cross-sectional study across nine districts of India. Issue 1 (24th December 2021) - Sharma, Shantanu; Rawat, Sucheta; Akhtar, Faiyaz; Singh, Rajesh Kumar; Mehra, Sunil
Abstract : Purpose: The authors intend to assess the village health sanitation and nutrition committees (VHSNC) on six parameters, including their formation, composition, meeting frequencies, activities, supervisory mechanisms and funds receipt and expenditures across nine districts of the three states of India. Design/methodology/approach: The cross-sectional study, conducted in the states of Uttar Pradesh (five districts), Odisha (two districts) and Rajasthan (two districts), used a quantitative research design. The community health workers of 140 VHSNCs were interviewed using a semi-structured questionnaire. The details about the funds' receipt and expenditures were verified from the VHSNC records (cashbook). Additionally, the authors asked about the role of health workers in the VHSNC meetings, and the issues and challenges faced. Findings: The average number of members in VHSNCs varied from 10 in Odisha to 15 in Rajasthan. Activities were regularly organized in Rajasthan and Odisha (one per month) compared to Uttar Pradesh (one every alternate month). Most commonly, health promotion activities, cleanliness drives, community monitoring and facilitation of service providers were done by VHSNCs. Funds were received regularly in Odisha compared to Rajasthan and Uttar Pradesh. Funds were received late and less compared to the demands or needs of VHSNCs. Research limitations/implications: This comprehensive analysis of VHSNCs' functioning in the selected study areas sheds light on the gaps in many components, including the untimely and inadequate receipt of funds, poor documentation of expenditures and involvement of VHSNC heads and inadequate supportive supervision. Originality/value: VHSNCs assessment has been done for improving community health governance.